2019
DOI: 10.3389/fevo.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Habitat Degradation Drives Neotropical Macrophyte Species Loss While Assisting the Spread of Invasive Plant Species

Abstract: aggressive species like Eichhornia, Azolla, and Egeria require hydrologically stable and eutrophic environments to spread; thus, management actions should focus on controlling these two factors. Our study demonstrates the need to use a long-term approach to fully-understand the effects of invasive macrophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
(124 reference statements)
2
17
0
Order By: Relevance
“…Human socioeconomic activities can affect plant invasion processes (Wu et al, 2010;Wang et al, 2011;Zhang et al, 2015;Egawa, 2017;Salgado et al, 2019;Zhu et al, 2019;Pyšek et al, 2020), which is consistent with our findings for Hainan. Among the 19 administrative units of the province, the administrative unit with the highest population and GDP, Haikou, had the highest PD and SR of non-native and invasive species.…”
Section: Discussion Distribution Patterns Of Non-native Species In Ha...supporting
confidence: 92%
See 1 more Smart Citation
“…Human socioeconomic activities can affect plant invasion processes (Wu et al, 2010;Wang et al, 2011;Zhang et al, 2015;Egawa, 2017;Salgado et al, 2019;Zhu et al, 2019;Pyšek et al, 2020), which is consistent with our findings for Hainan. Among the 19 administrative units of the province, the administrative unit with the highest population and GDP, Haikou, had the highest PD and SR of non-native and invasive species.…”
Section: Discussion Distribution Patterns Of Non-native Species In Ha...supporting
confidence: 92%
“…This suggests that reduction in the arrival of potentially invasive species in Hainan can be curbed by paying particular attention to arriving ships and aircraft from these areas. Various explanations emphasize that population density and GDP are key factors related to the composition, occurrence, and persistence of non-native species (Wu et al, 2010;Wang et al, 2011;Zhang et al, 2015;Salgado et al, 2019;Zhu et al, 2019). Generally, the higher the density of human residents, the higher the concentration of economic activities.…”
Section: Factors Affecting Non-native Plant Species In Hainanmentioning
confidence: 99%
“…The relative shallowness of these two lakes (< 8 m) could explain this synchronous pattern. In general, shallow lakes are regarded as dynamic, well‐mixed systems that respond quickly to climate and anthropogenic disturbance (Salgado et al 2019). In this regard, Aulacoseira taxa were dominant components in Yahuarcocha and Fondococha records as they are dependent on turbulence to remain in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the invasion of X. strumarium was prominent on the roads/wastes field sides in herb or shrub-dominated communities, and in agricultural fields. Similarly, [87][88][89][90][91] have predicted road pavements, railway tracks, and agricultural lands are most susceptible to plant invasion. Moreover, low diversity indexes were recorded which may correspond to the high invasion rate in the measured sites.…”
Section: Strumarium Invasion and Environmental Variablesmentioning
confidence: 99%